Value of ambulatory blood pressure measure in pregnancy hypertension - Correia, Ana; Leitão, Fátima (Clinical Journal of Obstetrics and Gynecology, 2018)
It is still not well known the prognostic cardiovascular value of 24h ambulatory blood pressure monitoring in the pregnant woman with hypertension. Objectives: Assess to the prognostic value of ABPM parameters in predicting maternofetal event. Methods: Retrospective and observational study which included 166 pregnant women. Results: The authors found that the night time DBP was the best predictor of adverse events. Non-dipper profile had worse survival at follow up until delivery compared to those with a dipper profile. Conclusions: ABPM is a tool for pregnant with HT because this is the unique method available that analyses the night blood pressure.